ANALYSIS OF CHITIN EXTRACTION AND ITS DEACETYLATION PROCESS (Scientific journal of the Fergana State University, 2024)
The current article discusses the stages of chitin extraction from insects (Melolontha melolontha, Leptinotarsa decemlinaeata, Eurygaster integriceps), the process of its deacetylation, and the factors affecting it, and the obtained results are presented.